Investigation on Three-Hump Phosphor-Coated White Light-Emitting Diodes for Healthy Lighting by Genetic Algorithm - Ziquan Guo; Kai Liu; Lili Zheng; Tien-mo Shih; Yijun Lu; Tingzhu Wu; Yi Lin; Yuxue Zhang; Jianghui Zheng; Jie Chen; Lianxin Chen; Zhong Chen (IEEE Photonics Journal, 2019)
In this paper, we carry out the theoretical spectral optimization and perform experiments by varying temperature and electrical current primarily on one-phosphor-coated three-hump white light-emitting diode (LED) for healthy indoor or outdoor lighting by using the genetic algorithm (GA). White light with low circadian action factor (CAF) is propitious for bedroom lighting to help people relax and to promote sleep, whereas high CAF white light is beneficial for increasing working efficiency in the working place. We obtain low CAF or high CAF according to different application occasions (such as bedroom lighting or office lighting), good Commission Internationale de L’Eclairage color rendering index ( $R_{a}$ ) or Illumination Engineering Society of North America color fidelity index ( $R_{f}$ ), and color gamut index ( $R_{g}$ ) or other color performances, and possibly high luminous efficacy of radiation (LER, $K$ ) at various correlated color temperatures (CCTs) from 2700 to 6500 K. For instance, in the case of one-phosphor-coated three-hump white LEDs at CCT = 3000 K, the low CAF as 0.264 ( $R_{a}$ = 80, $R_{f}$ = 77, $R_{g}$ = 103, and $K$ = 350.0 lm/W) can be achieved, whereas that of standard light at the same CCT is 0.407. In addition, we also compare four types of three-hump white LEDs in performances of circadian action, luminous efficacy of radiation (LER), and color rendering. This paper can help both industry and academia understand the application of three-hump white LEDs in the healthy indoor or outdoor lighting.